Penetapan Kadar Katekin dan Uji Aktivitas Antioksidan Dari Seduhan dan Ekstrak Etanol Biji Kakao (Theobroma cacao L.) Secara Spektrofotometri Uv-Vis - Dahnia Ayu Fitria; Anny Sartika Daulay; Ridwanto Ridwanto; Haris Munandar Nasution (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Cocoa beans (Theobroma cacao L.) are widely recognized as a rich source of bioactive polyphenolic compounds, particularly flavan-3-ols such as catechin and epicatechin, which exhibit potent antioxidant properties. These secondary metabolites play a critical role in neutralizing free radicals, thereby mitigating oxidative stress implicated in various degenerative diseases. Objective: This study aimed to compare catechin equivalent content and DPPH radical scavenging activity between ethanolic extract (maceration with 70% ethanol) and aqueous infusion (90°C, 15 min) of cocoa beans. Methods: Phytochemical screening was conducted qualitatively. Catechin equivalent content was determined using UV-Vis spectrophotometry at 280 nm, while antioxidant activity was evaluated using the DPPH method at 515 nm with vitamin C as positive control. Results: Both samples contained alkaloids, flavonoids, saponins, tannins, triterpenoids/steroids, polyphenols, and glycosides. The ethanolic extract exhibited higher catechin equivalent content (37.15 ± 0.07 µg/mL) compared to the infusion (19.83 ± 0.10 µg/mL), corresponding to 12.53 ± 0.72 mg/g and 11.18 ± 1.72 mg/g, respectively. The DPPH assay revealed superior antioxidant activity for the ethanolic extract (IC₅₀ = 83.29 µg/mL; strong category) compared to the infusion (IC₅₀ = 192.65 µg/mL; weak category), with vitamin C showing IC₅₀ = 2.95 µg/mL (very strong). Conclusion: Ethanolic maceration is more effective than aqueous infusion for extracting catechin equivalents and achieving higher antioxidant activity from cocoa beans. Further confirmation using HPLC-DAD or LC-MS is recommended to validate specific catechin concentrations.